A High-Quality Mach-Zehnder Interferometer Fiber Sensor by Femtosecond Laser One-Step Processing - Zhao, Longjiang (Molecular Diversity Preservation International (MDPI), 2010)
During new fiber sensor development experiments, an easy-to-fabricate simple sensing structure with a trench and partially ablated fiber core is fabricated by using an 800 nm 35 fs 1 kHz laser. It is demonstrated that the structure forms a Mach-Zehnder interferometer (MZI) with the interference between the laser light passing through the air in the trench cavity and that in the remained fiber core. The fringe visibilities are all more than 25 dB. The transmission spectra vary with the femtosecond (fs) laser ablation scanning cycle. The free spectral range (FSR) decreases as the trench length increases. The MZI structure is of very high fabrication and sensing repeatability. The sensing mechanism is theoretically discussed, which is in agreement with experiments. The test sensitivity for acetone vapor is about 10(4) nm/RIU, and the temperature sensitivity is 51.5 pm/°C at 200 ∼ 875 °C with a step of 25 °C.